Resource allocation based on interference coordination for Multicast-Broadcast Single Frequency Network (MBSFN) / Mohd Fahmi Azman - Mohd Fahmi , Azman (2013)
The Multimedia Broadcast Multicast Service (MBMS) in Long Term Evolution (LTE) becomes a new technique of delivering the data to the user. It can save the available spectrum since it is shared in one dedicated channel. With enormous development in wireless mobile communication, this service can be easily implemented to achieve high system capacity and system throughput. However, there will be an issue regarding the limited available resources in the heterogeneous system. Therefore, one technique has been adapted from Digital Video Broadcasting-Terrestrial (DVB-T) called Multimedia Broadcast Multicast Service over Single Frequency Networks (MBSFN). In MBSFN, the data content is transmitted synchronously from multiple transmitters in a respective area. The receiver will receive multiple signals and interpret it either it is useful or destructive so that it can differentiate which signal to process. Thus, this approach will improve the spectral efficiency of the signal by only selecting the constructive signal. However, the performance of MBSFN is still restricted in the area that closes to adjacent MBSFN areas due to the impact of external interference from neighbouring MBSFN area. The method to minimize the interference has been studied carefully. The strategy of allocating the resource by static or dynamic allocation can coordinate the interference issue. In static resource allocation, the fixed frequency allocation is to be planned for each MBSFN area by adopting the frequency reuse technique such as traditional frequency reuse and fractional frequency reuse. Likewise, in dynamic resource allocation, the resource is allocated dynamically based on the calculated interference level. Genetic algorithm has been implemented to find the solution of allocating the static of pool of frequency respectively to the MBSFN area and to coordinate its interference (SFA-GA). The impact of interference in each frequency reuse scheme has been evaluated by calculating its SINR. For dynamic resource allocation, we proposed the game theory technique to allocate the pool of resources (DRA-IC). SFA-GA would give the solution of how to allocate the frequency based on frequency reuse to the respective MBSFN area . Results show higher frequency reuse scheme reduce the impact of interference. However, in DRA-IC scheme give better performance compared to SFA-GA due to the allocated resources are dynamically distributed with better coordinated interference level.